The Global Crisis of Drug-Resistant Tuberculosis and Leadership of China and the BRICS: Challenges and Opportunities: Summary of a Joint Workshop by the Institute of Medicine and the Institute of Microbiology, Chinese Academy of Sciences - Institute of Medicine (The National Academies Press, 2014)
Multidrug-resistant tuberculosis (TB) is caused by bacteria resistant to isoniazid and rifampicin, the two most effective first-line anti-TB drugs, originally developed and introduced in the 1950 and 1960s. Since 2008, the Forum on Drug Discovery, Development, and Translation of the Institute of Medicine has hosted or co-hosted six domestic and international workshops addressing the global crisis of drug-resistant TB, with special attention to the BRICS countries - Brazil, Russia, India, China, and South Africa. The Global Crisis of Drug-Resistant Tuberculosis and Leadership of China and the BRICS is the summary of a workshop convened to address the current status of drug-resistant TB globally and in China. This report considers lessons learned from high burden countries; highlights global challenges to controlling the spread of drug-resistant strains; and discusses innovative strategies to advance and harmonize local and international efforts to prevent and treat drug-resistant TB. Additionally, the report examines the problem of MDR TB and emergent TB strains that are potentially untreatable with drugs available and considers the critical leadership role of the BRICS countries in addressing the threats and opportunities in drug-resistant TB.
Keywords: Health and Medicine

Global Health Impacts of Vector-Borne Diseases: Workshop Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Pathogens transmitted among humans, animals, or plants by insects and arthropod vectors have been responsible for significant morbidity and mortality throughout recorded history. Such vector-borne diseases – including malaria, dengue, yellow fever, and plague – together accounted for more human disease and death in the 17th through early 20th centuries than all other causes combined. Over the past three decades, previously controlled vector-borne diseases have resurged or reemerged in new geographic locations, and several newly identified pathogens and vectors have triggered disease outbreaks in plants and animals, including humans. Domestic and international capabilities to detect, identify, and effectively respond to vector-borne diseases are limited. Few vaccines have been developed against vector-borne pathogens. At the same time, drug resistance has developed in vector-borne pathogens while their vectors are increasingly resistant to insecticide controls. Furthermore, the ranks of scientists trained to conduct research in key fields including medical entomology, vector ecology, and tropical medicine have dwindled, threatening prospects for addressing vector-borne diseases now and in the future. In June 2007, as these circumstances became alarmingly apparent, the Forum on Microbial Threats hosted a workshop to explore the dynamic relationships among host, pathogen(s), vector(s), and ecosystems that characterize vector-borne diseases. Revisiting this topic in September 2014, the Forum organized a workshop to examine trends and patterns in the incidence and prevalence of vector-borne diseases in an increasingly interconnected and ecologically disturbed world, as well as recent developments to meet these dynamic threats. Participants examined the emergence and global movement of vector-borne diseases, research priorities for understanding their biology and ecology, and global preparedness for and progress toward their prevention, control, and mitigation. This report summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Rapid Medical Countermeasure Response to Infectious Diseases: Enabling Sustainable Capabilities Through Ongoing Public- and Private-Sector Partnerships: Workshop Summary - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Emerging infectious disease threats that may not have available treatments or vaccines can directly affect the security of the world's health since these diseases also know no boundaries and will easily cross borders. Sustaining public and private investment in the development of medical countermeasures (MCMs) before an emerging infectious disease becomes a public health emergency in the United States has been extremely challenging. Interest and momentum peak during a crisis and wane between events, and there is little interest in disease threats outside the United States until they impact people stateside. On March 26 and 27, 2015, the Institute of Medicine convened a workshop in Washington, DC to discuss how to achieve rapid and nimble MCM capability for new and emerging threats. Public- and private-sector stakeholders examined recent efforts to prepare for and respond to outbreaks of Ebola Virus Disease, pandemic influenza, and coronaviruses from policy, budget, and operational standpoints. Participants discussed the need for rapid access to MCM to ensure national security and considered strategies and business models that could enhance stakeholder interest and investment in sustainable response capabilities. This report summarizes the presentations and discussions from this workshop.
Keywords: Health and Medicine

The Domestic and International Impacts of the 2009-H1N1 Influenza A Pandemic: Global Challenges, Global Solutions: Workshop Summary - Institute of Medicine (The National Academies Press, 2010)
In March and early April 2009, a new, swine-origin 2009-H1N1 influenza A virus emerged in Mexico and the United States. During the first few weeks of surveillance, the virus spread by human-to-human transmission worldwide to over 30 countries. On June 11, 2009, the World Health Organization (WHO) raised the worldwide pandemic alert level to Phase 6 in response to the ongoing global spread of the novel influenza A (H1N1) virus. By October 30, 2009, the H1N1 influenza A had spread to 191 countries and resulted in 5,700 fatalities. A national emergency was declared in the United States and the swine flu joined SARS and the avian flu as pandemics of the 21st century. Vaccination is currently available, but in limited supply, and with a 60 percent effectiveness rate against the virus. The story of how this new influenza virus spread out of Mexico to other parts of North America and then on to Europe, the Far East, and now Australia and the Pacific Rim countries has its origins in the global interconnectedness of travel, trade, and tourism. Given the rapid spread of the virus, the international scientific, public health, security, and policy communities had to mobilize quickly to characterize this unique virus and address its potential effects. The World Health Organization and Centers for Disease Control have played critical roles in the surveillance, detection and responses to the H1N1 virus. The Domestic and International Impacts of the 2009-H1N1 Influenza A Pandemic: Global Challenges, Global Solutions aimed to examine the evolutionary origins of the H1N1 virus and evaluate its potential public health and socioeconomic consequences, while monitoring and mitigating the impact of a fast-moving pandemic. The rapporteurs for this workshop reported on the need for increased and geographically robust global influenza vaccine production capacities; enhanced and sustained interpandemic demand for seasonal influenza vaccines; clear "triggers" for pandemic alert levels; and accelerated research collaboration on new vaccine manufacturing techniques. This book will be an essential guide for healthcare professionals, policymakers, drug manufacturers and investigators.
Keywords: Health and Medicine

Global Health Risk Framework: Research and Development of Medical Products: Workshop Summary - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Since the 2014 Ebola outbreak many public- and private-sector leaders have seen a need for improved management of global public health emergencies. The effects of the Ebola epidemic go well beyond the three hardest-hit countries and beyond the health sector. Education, child protection, commerce, transportation, and human rights have all suffered. The consequences and lethality of Ebola have increased interest in coordinated global response to infectious threats, many of which could disrupt global health and commerce far more than the recent outbreak. In order to explore the potential for improving international management and response to outbreaks the National Academy of Medicine agreed to manage an international, independent, evidence-based, authoritative, multistakeholder expert commission. As part of this effort, the Institute of Medicine convened four workshops in summer of 2015 to inform the commission report. The presentations and discussions from the Workshop on Research and Development of Medical Products are summarized in this report.
Keywords: Health and Medicine

Global Health and the Future Role of the United States - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
While much progress has been made on achieving the Millenium Development Goals over the last decade, the number and complexity of global health challenges has persisted. Growing forces for globalization have increased the interconnectedness of the world and our interdependency on other countries, economies, and cultures. Monumental growth in international travel and trade have brought improved access to goods and services for many, but also carry ongoing and ever-present threats of zoonotic spillover and infectious disease outbreaks that threaten all. Global Health and the Future Role of the United States identifies global health priorities in light of current and emerging world threats. This report assesses the current global health landscape and how challenges, actions, and players have evolved over the last decade across a wide range of issues, and provides recommendations on how to increase responsiveness, coordination, and efficiency – both within the U.S. government and across the global health field.
Keywords: Health and Medicine

Global Health Risk Framework: Resilient and Sustainable Health Systems to Respond to Global Infectious Disease Outbreaks: Workshop Summary - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Since the 2014 Ebola outbreak many public- and private-sector leaders have seen a need for improved management of global public health emergencies. The effects of the Ebola epidemic go well beyond the three hardest-hit countries and beyond the health sector. Education, child protection, commerce, transportation, and human rights have all suffered. The consequences and lethality of Ebola have increased interest in coordinated global response to infectious threats, many of which could disrupt global health and commerce far more than the recent outbreak. In order to explore the potential for improving international management and response to outbreaks the National Academy of Medicine agreed to manage an international, independent, evidence-based, authoritative, multistakeholder expert commission. As part of this effort, the Institute of Medicine convened four workshops in summer of 2015 to inform the commission report. The presentations and discussions from the Workshop on Resilient and Sustainable Health Systems to Respond to Global Infectious Disease Outbreaks are summarized in this report.
Keywords: Health and Medicine

Integrating Clinical Research into Epidemic Response: The Ebola Experience - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The 2014–2015 Ebola epidemic in western Africa was the longest and most deadly Ebola epidemic in history, resulting in 28,616 cases and 11,310 deaths in Guinea, Liberia, and Sierra Leone. The Ebola virus has been known since 1976, when two separate outbreaks were identified in the Democratic Republic of Congo (then Zaire) and South Sudan (then Sudan). However, because all Ebola outbreaks prior to that in West Africa in 2014–2015 were relatively isolated and of short duration, little was known about how to best manage patients to improve survival, and there were no approved therapeutics or vaccines. When the World Heath Organization declared the 2014-2015 epidemic a public health emergency of international concern in August 2014, several teams began conducting formal clinical trials in the Ebola affected countries during the outbreak. Integrating Clinical Research into Epidemic Response: The Ebola Experience assesses the value of the clinical trials held during the 2014–2015 epidemic and makes recommendations about how the conduct of trials could be improved in the context of a future international emerging or re-emerging infectious disease events.
Keywords: Health and Medicine

Crossing the Global Quality Chasm: Improving Health Care Worldwide - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
In 2015, building on the advances of the Millennium Development Goals, the United Nations adopted Sustainable Development Goals that include an explicit commitment to achieve universal health coverage by 2030. However, enormous gaps remain between what is achievable in human health and where global health stands today, and progress has been both incomplete and unevenly distributed. In order to meet this goal, a deliberate and comprehensive effort is needed to improve the quality of health care services globally. Crossing the Global Quality Chasm: Improving Health Care Worldwide focuses on one particular shortfall in health care affecting global populations: defects in the quality of care. This study reviews the available evidence on the quality of care worldwide and makes recommendations to improve health care quality globally while expanding access to preventive and therapeutic services, with a focus in low-resource areas. Crossing the Global Quality Chasm emphasizes the organization and delivery of safe and effective care at the patient/provider interface. This study explores issues of access to services and commodities, effectiveness, safety, efficiency, and equity. Focusing on front line service delivery that can directly impact health outcomes for individuals and populations, this book will be an essential guide for key stakeholders, governments, donors, health systems, and others involved in health care.
Keywords: Health and Medicine

Engaging the Private-Sector Health Care System in Building Capacity to Respond to Threats to the Public's Health and National Security: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Disasters tend to cross political, jurisdictional, functional, and geographic boundaries. As a result, disasters often require responses from multiple levels of government and multiple organizations in the public and private sectors. This means that public and private organizations that normally operate independently must work together to mount an effective disaster response. To identify and understand approaches to aligning health care system incentives with the American public's need for a health care system that is prepared to manage acutely ill and injured patients during a disaster, public health emergency, or other mass casualty event, the National Academies of Sciences, Engineering, and Medicine hosted a 2-day public workshop on March 20 and 21, 2018. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine; Conflict and Security Issues

Regional Disaster Response Coordination to Support Health Outcomes: Summary of a Workshop Series - Institute of Medicine (The National Academies Press, 2015)
When disaster strikes, it rarely impacts just one jurisdiction. Many catastrophic disaster plans include support from neighboring jurisdictions that likely will not be available in a regional disaster. Bringing multiple stakeholders together from sectors that do not routinely work with each other can augment a response to a disaster, but can also be extremely difficult because of the multi-disciplinary communication and coordination needed to ensure effective medical and public health response. As many communities within a region will have similar vulnerabilities, a logical step in planning is to establish responsibilities and capacities, and be able to work toward common goals to address all-hazards when the entire region is affected. To explore these considerations, the Institute of Medicine's Forum on Medical and Public Health Preparedness for Catastrophic Events organized a series of three regional workshops in 2014 to explore opportunities to strengthen the regional coordination required in response to a large scale multijurisdictional disaster. The purpose of each regional workshop was to discuss ways to strengthen coordination among multiple jurisdictions in various regions to ensure fair and equitable treatment of communities from all impacted areas. Regional Disaster Response Coordination to Support Health Outcomes summarizes the presentation and discussion of these workshops.
Keywords: Health and Medicine; Conflict and Security Issues

Enabling Rapid and Sustainable Public Health Research During Disasters: Summary of a Joint Workshop by the Institute of Medicine and the U.S. Department of Health and Human Services - Institute of Medicine (The National Academies Press, 2015)
Over the past decade, preparedness and response capacities of government agencies, hospitals and clinics, public health agencies, and academic researchers in the United States and abroad have been challenged by a succession of public health emergencies, ranging from radiological threats to pandemics to earthquakes. Through After Action Reports, each of these emergencies has yielded important information and lessons learned that can inform future disaster response and recovery efforts. However, important information that needs to be collected during and immediately following these emergencies is often missed because of barriers and obstacles to gathering such data, such as varying institutional review board restrictions in different states, no sustainable funding network for this type of work, uncertainty on who should be involved in research response, and a lack of knowledge around how best to integrate research into response and recovery frameworks. Taking action to enable medical and public health research during disasters was the focus of a workshop held on June 12 and 13, 2014, coordinated and supported jointly by the Institute of Medicine Forum on Medical and Public Health Preparedness for Catastrophic Events, National Institute of Environmental Health Sciences, the National Library of Medicine, the U.S. Department of Health and Human Services' Office of the Assistant Secretary for Preparedness and Response, and the Centers for Disease Control and Prevention. Invited speakers and participants from federal, state, and local government, academia, and community and worker organizations came together to discuss how to integrate research into existing response structures; identify critical research needs and priorities; identify obstacles and barriers to research; discuss structures and strategies needed for deployment of a research study; share ideas, innovations, and technologies to support research; and explore data collection tools and data-sharing mechanisms for both rapid and longitudinal research. Enabling Rapid and Sustainable Public Health Research During Disasters summarizes the presentations and discussion of the workshop.
Keywords: Health and Medicine; Conflict and Security Issues

Infectious Disease Movement in a Borderless World: Workshop Summary - Institute of Medicine (The National Academies Press, 2010)
Modern transportation allows people, animals, and plants—and the pathogens they carry—to travel more easily than ever before. The ease and speed of travel, tourism, and international trade connect once-remote areas with one another, eliminating many of the geographic and cultural barriers that once limited the spread of disease. Because of our global interconnectedness through transportation, tourism and trade, infectious diseases emerge more frequently; spread greater distances; pass more easily between humans and animals; and evolve into new and more virulent strains. The IOM's Forum on Microbial Threats hosted the workshop "Globalization, Movement of Pathogens (and Their Hosts) and the Revised International Health Regulations" December 16-17, 2008 in order to explore issues related to infectious disease spread in a "borderless" world. Participants discussed the global emergence, establishment, and surveillance of infectious diseases; the complex relationship between travel, trade, tourism, and the spread of infectious diseases; national and international policies for mitigating disease movement locally and globally; and obstacles and opportunities for detecting and containing these potentially wide-reaching and devastating diseases. This document summarizes the workshop.
Keywords: Health and Medicine; Conflict and Security Issues

What You Need to Know About Infectious Disease - Institute of Medicine (The National Academies Press, 2011)
About a quarter of deaths worldwide--many of them children--are caused by infectious organisms. The World Health Organization reports that new infectious diseases are continuing to emerge and familiar ones are appearing in new locations around the globe. What's behind this trend? How can invisible organisms cause such harm? And to what extent has human behavior amplified the problem? What You Need to Know About Infectious Disease provides an overview of infectious disease, drawing on reports of the Institute of Medicine. Written for a general audience, it describes the biology, history, and future trends of some of the world's most widespread and harmful infections and explains what we need to do--as individuals and as a society--to address this global challenge.
Keywords: Health and Medicine

Vector-Borne Diseases: Understanding the Environmental, Human Health, and Ecological Connections: Workshop Summary - Institute of Medicine (The National Academies Press, 2008)
Vector-borne infectious diseases, such as malaria, dengue fever, yellow fever, and plague, cause a significant fraction of the global infectious disease burden; indeed, nearly half of the world's population is infected with at least one type of vector-borne pathogen (CIESIN, 2007; WHO, 2004a). Vector-borne plant and animal diseases, including several newly recognized pathogens, reduce agricultural productivity and disrupt ecosystems throughout the world. These diseases profoundly restrict socioeconomic status and development in countries with the highest rates of infection, many of which are located in the tropics and subtropics. Although this workshop summary provides an account of the individual presentations, it also reflects an important aspect of the Forum philosophy. The workshop functions as a dialogue among representatives from different sectors and allows them to present their beliefs about which areas may merit further attention. These proceedings summarize only the statements of participants in the workshop and are not intended to be an exhaustive exploration of the subject matter or a representation of consensus evaluation. Vector-Borne Diseases : Understanding the Environmental, Human Health, and Ecological Connections, Workshop Summary (Forum on Microbial Threats) summarizes this workshop.
Keywords: Health and Medicine; Conflict and Security Issues

Understanding the Economics of Microbial Threats: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Microbial threats, including endemic and emerging infectious diseases and antimicrobial resistance, can cause not only substantial health consequences but also enormous disruption to economic activity worldwide. While scientific advances have undoubtedly strengthened our ability to respond to and mitigate the mortality of infectious disease threats, events over the past two decades have illustrated our continued vulnerability to economic consequences from these threats. To assess the current understanding of the interaction of infectious disease threats with economic activity and suggest potential new areas of research, the National Academies of Sciences, Engineering, and Medicine planned a 1.5-day public workshop on understanding the economics of microbial threats. This workshop built on prior work of the Forum on Microbial Threats and aimed to help transform current knowledge into immediate action. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

The Impact of Globalization on Infectious Disease Emergence and Control: Exploring the Consequences and Opportunities: Workshop Summary - Institute of Medicine (The National Academies Press, 2006)
Globalization is by no means a new phenomenon; transcontinental trade and the movement of people date back at least 2,000 years, to the era of the ancient Silk Road trade route. The global spread of infectious disease has followed a parallel course. Indeed, the emergence and spread of infectious disease are, in a sense, the epitome of globalization. Although some experts mark the fall of the Berlin Wall as the beginning of this new era of globalization, others argue that it is not so new. The future of globalization is still in the making. Despite the successful attempts of the developed world during the course of the last century to control many infectious diseases and even to eradicate some deadly afflictions, 13 million people worldwide still die from such diseases every year. On April 16 and 17, 2002, the Forum on Emerging Infections held a working group discussion on the influence of globalization on the emergence and control of infectious diseases. The contents of the unattributed sections are based on the presentations and discussions that took place during the workshop. The Impact of Globalization on Infectious Disease Emergence and Control report summarizes the presentations and discussions related to the increasing cross-border and cross-continental movements of people and how this could exacerbate the emergence and global spread of infectious diseases. This report also summarizes the means by which sovereign states and nations must adopt a global public health mind-set and develop a new organizational framework to maximize the opportunities and overcome the challenges created by globalization and build the necessary capacity to respond effectively to emerging infectious disease threats.
Keywords: Health and Medicine

International Infectious Disease Emergencies and Domestic Implications for the Public Health and Health Care Sectors: Workshop in Brief - Institute of Medicine (The National Academies Press, 2015)
Emerging infectious disease events present a threat to U.S. national security, and we need improved efforts to coordinate a response both domestically and with global partners. The most recent outbreak of the Ebola virus disease in West Africa is the largest to date, affecting multiple countries simultaneously and once again bringing the challenges of global health security to the forefront of international preparedness discussions. The outbreak in the United States exposed health care system gaps and brought to a head the need for increased communication between hospitals and health departments and the need for clearer direction and coordination from state and federal agencies on operational standards and practices. This Workshop in Brief summarizes a session held by the Institute of Medicine's (IOM's) Forum on Medical and Public Health Preparedness for Catastrophic Events at the 2015 Preparedness Summit to discuss international public health emergencies, such as Ebola, and their corresponding impact on state and local public health and health care systems.
Keywords: Health and Medicine

Gain-of-Function Research: Summary of the Second Symposium, March 10-11, 2016 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
On March 10-11, 2016, the National Academies of Sciences, Engineering, and Medicine held a public symposium on potential U.S. government policies for the oversight of gain-of- function (GOF) research. This was the Academies' second meeting held at the request of the U.S. government to provide a mechanism to engage the life sciences community and the broader public and solicit feedback on optimal approaches to ensure effective federal oversight of GOF research as part of a broader U.S. government deliberative process. The first symposium, held in December 2014, examined the underlying scientific and technical questions surrounding the potential risks and benefits of GOF research involving pathogens with pandemic potential. The second symposium focused on discussion of the draft recommendations regarding GOF research of a Working Group of the National Science Advisory Board for Biosecurity. This report summarizes the key issues and ideas identified during the second symposium.
Keywords: Health and Medicine

Building Communication Capacity to Counter Infectious Disease Threats: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Building communication capacity is a critical piece of preparing for, detecting, and responding to infectious disease threats. The International Health Regulations (IHR) establish risk communication—the real-time exchange of information, advice, and opinions between experts or officials and people who face a threat to their survival, health, and economic or social well-being—as a core capacity that World Health Organization member states must fulfill to strengthen the fight against these threats. Despite global recognition of the importance of complying with IHR, 67 percent of signatory countries report themselves as not compliant. By investing in communication capacity, public health and government officials and civil society organizations facing health crises would be prepared to provide advice, information, and reassurance to the public as well as to rapidly develop messages and community engagement activities that are coordinated and take into account social and behavioral dynamics among all sectors. To learn about current national and international efforts to develop the capacity to communicate effectively during times of infectious disease outbreaks, and to explore gaps in the research agenda that may help address communication needs to advance the field, the Forum on Microbial Threats of the National Academies of Sciences, Engineering, and Medicine convened a 1.5 day workshop on December 13 and 14, 2016, in Washington, DC. Participants reviewed progress and needs in strengthening communication capacity for dealing with infectious disease threats for both outbreaks and routine challenges in the United States and abroad. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine